Reconstruction of post-burn hand contractures with Trapeze flap: Trapeze flap on post-burn hand - Fattah, Jalal Hamasalih (Cellular and Molecular Biology, 2022)
Finger scar flexion contractures are a leading cause of hand disability and a serious complication of hand burns. There are numerous reconstructive procedures available nowadays. Nevertheless, a large number of them produce disappointing results. The goal is to assess the Trapeze flap's ability to repair post-burn finger flexion contractures. Also, the stromal cell-derived factor 1 (SDF1) gene expression was examined for further evaluation. From April 2014 to February 2020, a prospective investigation was undertaken at Rizgary teaching and CMC private hospitals in Erbil (in Iraq) to consider the effect of Trapeze flaps on the correction of postburn flexion contracture of fingers and first web space in 67 patients (112 fingers). The viability of flaps, complications, skin graft take, and also surgeon/patient satisfaction were all recorded. Follow-up outcomes were collected from 6 months to a year after the operation. Further, the qPCR technique was used to evaluate the expression of the SDF1 gene in two groups of patients. The first group included those 67 patients treated with the trapeze flap method. The other group consisted of 50 patients with post-burn hands who were not treated by this method. Our survey found that approximately 97 percent of patients were satisfied (65 out of 67). A rare consequence included partial flap loss (one patient, 1.5 percent), and infection was detected in one case (1.5 percent ). Both wounds healed with conservative treatment. The postoperative scars were practically imperceptible, without hypertrophic scars or keloid construction, and the surface texture of the flaps was similar to the texture of healthy fingers. The contractures did not occur again. Also, the expression of the SDF1 gene showed that the trapeze flap method caused a statistically increased expression. This gene stimulates collagen production during the repair of injuries. Generally, the trapeze flap is a dependable and successful local flap in recreating hand post-burn contracture, resulting in extreme patient satisfaction and achievement.